PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IX PADA MATA PELAJARAN FIQIH DI MTS AL-ISLAM JAMSAREN SURAKARTA TAHUN AJARAN 2024/2025 - Rohmah, Mar-Atin Nabila; Nashir, Muhammad Ja’far (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This research aims to: (1) To find out the application of problem-based learning model for class IX students in understanding fiqh at MTs Al-Islam Jamsaren Surakarta. (2) To determine the critical thinking skills of grade IX students in fiqh subjects at MTs Al-Islam Jamsaren Surakarta. (3) To determine the effect of problem-based learning model on critical thinking ability of grade IX students in fiqh subject at MTs Al Islam Jamsaren Surakarta. Based on the results of data analysis it can be concluded that: (1) The problem-based learning model is not the main factor in students` critical thinking skills in fiqh subjects, but a form of strategy variation in learning so that students are not easily bored. (2) The results of the critical thinking skills of ninth grade students in Fiqh subjects at MTs Al-Islam Jamsaren Surakarta show an average of 58. 73, with a median value of 59. (3) The effect between problem-based learning and critical thinking skills of grade IX students in Fiqh subjects at MTs Al-Islam Jamsaren Surakarta in the 2024/2025 school year shows that there is no significant influence.